2011
DOI: 10.1089/aid.2010.0291
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Toxicity-Related Regimen Changes in the Development of Antiretroviral Resistance

Abstract: In an effort to evaluate factors associated with the development of antiretroviral (ARV) resistance, we assessed the prevalence of toxicity-related regimen changes and modeled its association to the subsequent development of ARV resistance in a cohort of treatment-naive individuals initiating ARV therapy (ART). A retrospective analysis of patients initiating ART was conducted at the UAB 1917 Clinic from 1 January 2000 to 30 September 2007. Cox proportional hazards models were fit to identify factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The reasons and risk factors for HAART regimen changes have been assessed by studies from resource-rich and resource-limited settings [ 13 17 ]. Similarly, in Ethiopia, some studies determined factors contributed to ART regimen change [ 12 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons and risk factors for HAART regimen changes have been assessed by studies from resource-rich and resource-limited settings [ 13 17 ]. Similarly, in Ethiopia, some studies determined factors contributed to ART regimen change [ 12 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 Even if few patients had their initial regimen changed due to stock-outs and adherence issue, it might contribute its own share for the overall drug resistance and present a challenge to limited treatment options that we currently have for these patients. 18,31 To this end, it is important is to maintain uninterrupted supplies of ART drugs in resource limited settings. 32 Patient awareness about HIV/AIDS treatment should also be improved to solve adherence problems.…”
Section: Discussionmentioning
confidence: 99%
“…The overall burden of ART regimen changing was relatively lower than rates that have been reported in other studies. This might be due to the introduction of combined fixed-dose combination drugs that are less toxic and more potent [2, 8, 14, 19]. A study conducted by Cotte et al, reported ART modifications to be higher in patients on daily multiple drug regimens than those on FDC [23].…”
Section: Discussionmentioning
confidence: 99%